Observations on the Jemjem Zebu cattle - Girma, A.; Frew, K. (2001)
An attempt was made to collect data for the purpose of describing Black (Jemjem) zebu cattle in the area of Kibre-Mengist in Oromiya Region, southern Ethiopia. The coat colour of these animals is predominantly black. Mean height at withers is 106cm. and heart girth is 134 cm. A high degree of uniformity particularly in coat colour was noted in the cattle population examined at Bore than at Kibre-Mengist, suggesting that the home of true type Jemjem Zebu is Bore. It is recommended that any future attempt to characterise this cattle type (e.g. molecular characterisation) should focus on the population found around Bore.